Penyuluhan dan Program Pemberdayaan Masyarakat dengan Membuat Minuman Sehat Anti Kolesterol - Fakhriyah Fakhriyah; Hesly Yanti; Hildayana Hildayana; Husnatul’Athiyyah; Hidayati Hidayati; Humaira Afifah (Jurnal Informasi Pengabdian Masyarakat, 2023)
According to the 2013 Basic Health Research as much as 69.9% of Indonesia's population is in a condition of hypercholesterolemia, most of it occurs in the male gender. Based on Posbindu data which was carried out in Wonorejo Village, RT 8, Satui District on February 9, 2022, which was carried out on 53 residents, it was found that 12 people had cholesterol levels above 200 mg/dL with a percentage of 22.64% affected by cholesterol. Intervention activities were in the form of counseling to the community was carried out using the lecture method and a community empowerment program was also held by making healthy anti-cholesterol drinks. The community is expected to always maintain good health in order to avoid high cholesterol by maintaining a healthy lifestyle and carrying out physical activity as needed.